Ten Years of Experience in Treating Patients With Digoxin Toxicity Without Using Digoxin Fab Antibody: Treating patients with digoxin toxicity without the use of Digoxin Fab antibodies - Gheshlaghi, Farzad; Wong, Anselm; Dorooshi, Gholamali; Meamar, Rokhsareh; Tabesh, Faezeh; Aminsafaei, Hajar; Zoofaghari, Shafeajafar; Eizadi-Mood, Nastaran (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Digoxin is extensively prescribed for cardiac diseases, so its chronic or acute toxicity commonly occur. Although digoxin specific antibodies (anti-digoxin Fab) are recommended to be used in patients with cardiac symptoms of digoxin toxicity, there is ongoing controversy about the effectiveness and dose of anti-digoxin Fab. Because our department lacks access to anti-digoxin Fab and the high cost of the antidote, we evaluated 10 years of experience in treating patients with digoxin toxicity without using digoxin Fab antibodies considering outcomes. Methods: A retrospective study was performed in Khorshid Hospital, affiliated with Isfahan University of Medical Sciences, from October 2008 to September 2018. Patients with acute or chronic digoxin toxicity were included in the study. The patients’ data were gathered and analyzed according to their medical documents. Results: Out of 150 cases with digoxin toxicity, 38% (n=57) were acute and 62% (n=93) were chronic. About 64.7% (n=97) were female. The most common non-cardiac manifestations of toxicity were gastrointestinal (67.3%, n=101) and neurological symptoms (52.7%, n=79). Bradyarrhythmia (80.5%, n=33) was the most cardiac manifestation in patients with acute (15.8% n=9) and chronic (25.8%, n=24) toxicity. A total of 144 (96%) cases fully recovered with supportive care, and 6 patients (4%) died. None of the cases received anti-digoxin Fab. Conclusion: The majority of presentations with acute or chronic toxicity recovered with supportive measures without using anti-digoxin Fab.